Urban geographic processes of settlements network of Ljig municipality - Matijević Dragana (Glasnik Srpskog Geografskog Društva, 2005)
Principles of modern development of settlements are taking place under the strong influence of great urban agglomerations. Belgrade and its gravitational role have triggered huge spatial and populational changes with distinctive differences within its metropolitan area. In northern parts of Belgrade functional zone, there are zones of strong concentration of population and economy, as opposed to southern parts, where depopulation and dissection of economy and activities are present. As a part of Belgrade functional area, settlements network of Ljig municipality has been subject to considerable urban-geographic changes. This paper gives the analysis of all changes in settlements network which occurred as a consequence of gravitational impacts of the capital.